Biotic enhancement of Desulfovibrio desulfuricans on multi-factor influenced corrosion of X80 steel in saline soil. (15th May 2022) - Qin, Qingyu; Xu, Jin; Wei, Boxin; Fu, Qi; Yu, Changkun; Sun, Cheng; Wang, Zhenyao
Abstract: The corrosion behavior of X80 steel in the condition presence of AC, Desulfovibrio desulfuricans and elastic stress was investigated in saline soil. D. desulfuricans and AC promoted the pitting corrosion, giving rise to crack initiation when the stress was applied. The corrosion rate of X80 steel in the three-factor system was the highest, reaching 0.535 mm a −1 . The synergistic factor of D. desulfuricans was larger than other two factors, indicating microbes played a critical role in enhancing the synergistic effect of AC, D. desulfuricans, and stress. Highlights: Synergistic corrosion of AC, SRB and stress was studied. Corrosion rate with AC, SRB and stress was 26 times higher than the control one. The synergistic effects with microbial factor on steel corrosion were larger. Biotically synergistic enhancement played a critical role in multifactor corrosion.